Transcranial direct current stimulation effects on cortical excitability and learning during a dorsiflexion motor task - Gomez-Guerrero, Gonzalo (2019)
Transcranial direct current stimulation (tDCS) is a method that could induce changes on the corticospinal excitability and enhanced motor learning. Nevertheless, research on the topic still ongoing due to the great variability of the corticospinal response and different methodologies that has been used with this device. Moreover, there is not much evidence on how it could affect to the lower limbs. Therefore, the aim of this study is to see what are the effects of a long-term exposure to tDCS and if they are maintained after its exposure. Thirteen right-footed healthy participants were recruited that were double blind and randomly assigned to different groups SHAM or STIM condition. They performed a motor task during 5 days and it was assessed 8 days after the last practice. Corticospinal measurements I/O curve, SICI and silent period were assessed before and after day 1,5 and retention day. Motor task consisted in following a sinusoidal curve displayed on a screen with an isometric force applied through a dorsiflexion of the ankle muscles. Result were no significant improvement from SHAM group from pre-to-post measurements on day 1. Non-significant results were found in the rest of the conditions, motor task error, Input/output curve, SICI or cortical Silent Period due to the dispersion of the data. Therefore, it cannot be concluded that tDCS will enhance the motor learning. However, it does increase the variability of the corticospinal excitability after its use.